1988
DOI: 10.2135/cropsci1988.0011183x002800020024x
|View full text |Cite
|
Sign up to set email alerts
|

Canopy Development, Yield, and Market Quality in Peanut as Affected by Genotype and Planting Pattern

Abstract: Planting peanut (Arachis hypogaea L.) in narrow rows with greater spacing between plants in order to approach a square pattern of plant arrangement can reduce competition and increase growth, especially during juvenility. Thus, this study was designed to assess the effects of planting pattern, genotype, and their interaction on seasonal vegetative growth, fruit growth and development, pod and kernel yields, and market quality. Seven genotypes, ‘Florunner’, ‘Tamnut’, and five experimental lines were used. Plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
2

Year Published

1989
1989
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 0 publications
1
32
2
Order By: Relevance
“…Williams (32) for groundnut in Rhodesia,and Pixleyet al (24,25) for peanut in Florida. Our maximum leaf area indexes (Fig.7) did not approach the higher values reported by Jaaffar and Gardner (15). However, they used a different technique based on a subsample and total dry weights of peanut plants, and may not have had as much foliar disease pressure.…”
Section: Cultivar Characteristicscontrasting
confidence: 64%
See 1 more Smart Citation
“…Williams (32) for groundnut in Rhodesia,and Pixleyet al (24,25) for peanut in Florida. Our maximum leaf area indexes (Fig.7) did not approach the higher values reported by Jaaffar and Gardner (15). However, they used a different technique based on a subsample and total dry weights of peanut plants, and may not have had as much foliar disease pressure.…”
Section: Cultivar Characteristicscontrasting
confidence: 64%
“…Studies on the effects of environmental conditions (6,13), agronomic practices (15,20), and disease and insect pressure (3,17,21,31) on peanuttypicallyinclude information on various growth characteristics, such as leafarea and plant dryweight. Many studies on peanut culture focus only on the endproducts ofyield and grade (7,16,17).…”
mentioning
confidence: 99%
“…Most studies have shown variable rates of canopy closure during early growth among groundnut cultivars grown at different plant population densities (Jaaffar & Gardner, 1988). This has been associated with differences in canopy structure (Mozingo, Coffelt & Wynne, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, canopy structure may affect groundnut responses to plant population density in terms of solar radiation interception and growth of the crop (Jaaffar & Gardner, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Spatial arrangement has been quantified as the mean rectangularity, or the ratio of distance between rows to the distance between plants within a row (e.g., Fawcett 1964, Nerson 1980, Jaaffar and Gardner 1988, Sutherland et al 1989. The influence of rectangularity has been quantified by measuring mean population yield rather than individual plant yield within the population.…”
Section: Introductionmentioning
confidence: 99%